Fishing Performance and Marketing Channel of the Marine Fisheries: An Empirical Study Using Primary and Secondary Data - Md. Abdul, Quddus; M. Muchlesur, Rahman; Zarin, Tasnim (INTI International University, 2024)
The Bay of Bengal is an important resourceful asset of Bangladesh, which has a lot of impact on the economy through its proper use. Marine fish and fishermen are the essential mechanisms for the economy. Thus, the investigation was undertaken to explore the assessment of marine fishing performance and fish marketing channels. Two marine fishing locations and 90 marine fishermen were selected. Information was gathered with a structured interview schedule. About 50% of fishing crafts were large; 8 to 17 fishermen operated those in the deep region of the Bay of Bengal and the majority of them (52.2%) were rented. About 48% of fishermen used their gear, 51% had large gear mostly rented and 54.4% received loans with interest from traders, banks, and NGOs. Shrimp/prawn production is lucrative for marine fishers and supportive of the national economy. The major problems faced by most of the fishermen of the two locations were the weather, engine breakdown, and prohibition of fishing time and Robbers in the Moheshkhali deep sea, whereas the use of pass cards, wild animals, protection by forest office and use of poison in Mongla. There are four marketing channels for marine fish and most (81%) sell to the whole sellers. A present marine fish marketing channel is more timeconsuming for a great number of intermediaries, insufficient road links and landing points/centers. To minimize this problem, modern information technology should be introduced, set up collective markets at coastal landing places, and reduce the number of middlemen.